Recent advancements in our understanding of equid gammaherpesvirus infections. (1st October 2021) - Easton‐Jones, Charlotte
Abstract: Equid gammaherpesviruses are ubiquitous and widespread in the equine population. Despite their frequent detection, their contribution to immune system modulation and the pathogenesis of several diseases remains unclear. Genetic variability and the combination of equid gammaherpesvirus strains a horse is infected with might be clinically significant. Initial gammaherpesvirus infection occurs in foals peripartum with latency then established in peripheral blood mononuclear cells. A novel EHV‐5 study suggests that following inhalation equid gammaherpesviruses might obtain direct access to T and B lymphocytes via the tonsillar crypts to establish latency. EHV‐5 is associated with equine multinodular pulmonary fibrosis, however, unlike with EHV‐2 there is currently minimal evidence for its role in milder cases of respiratory disease and poor performance. Transmission is presumed to be via the upper respiratory tract with periodic reactivation of the latent virus in adult horses. Stress of transport has been identified as a risk factor for reactivation and shedding of equine gammaherpesviruses. There is currently a lack of evidence for the effectiveness of antiviral drugs in the treatment of equine gammaherpesvirus infections.